Weaknesses Of Judges Thinking In Civil Law Systems - Made Hendra Wijaya (Sociological Jurisprudence Journal, 2021)
Judge’s an instrument of justice that are at the forefront in enforce the justice in society, but sometime the judge’s decision does not represent justice in society, because the judge’s in conducting the trial should follow existing the systems. Just as judge’s as adherent of the civil law system. In this paper describes the civil law system, started from Roman era, German, Francis, as well as elements of a definition of the civil law systems, and then discusses the judges in the civil law system, and discuss any weaknesses civil law2 judges in terms of implementing the trial in finding justice in society.